Multifunctional Bioactivity Electrospinning Nanofibers Encapsulating Emodin Provides a Potential Postoperative Management Strategy for Skin Cancer - Peiwen Ye; Reyisha Yusufu; Zhenfeng Guan; Tiantian Chen; Siyi Li; Yanping Feng; Xiaoyan Zeng; Jingya Lu; Muxiang Luo; Fenghuan Wei (MDPI AG, 2024)
Skin cancer is threatening more and more people's health; its postoperative recurrence and wound infection are still critical challenges. Therefore, specialty wound dressings with multifunctional bioactivity are urgently desired. Emodin is a natural anthraquinone compound that has anti-cancer and anti-bacterial properties. Herein, we fabricated coaxial electrospinning nanofibers loaded with emodin to exploit a multifunctional wound dressing for skin cancer postoperative management, which encapsulated emodin in a polyvinylpyrrolidone core layer, combined with chitosan-polycaprolactone as a shell layer. The nanofibers were characterized via morphology, physicochemical nature, drug load efficiency, pH-dependent drug release profiles, and biocompatibility. Meanwhile, the anti-cancer and anti-bacterial effects were evaluated in vitro. The emodin-loaded nanofibers exhibited smooth surfaces with a relatively uniform diameter distribution and a clear shell-core structure; remarkably, emodin was evenly dispersed in the nanofibers with significantly enhanced dissolution of emodin. Furthermore, they not only display good wettability, high emodin entrapment efficiency, and biphasic release profile but also present superior biocompatibility and anti-cancer properties by increasing the levels of MDA and ROS in A-375 and HSC-1 cells via apoptosis-related pathway, and long-term anti-bacterial effects in a dose-independent manner. The findings indicate that the emodin-loaded nanofiber wound dressing can provide a potential treatment strategy for skin cancer postoperative management.